A first look into radiomics application in testicular imaging: A systematic review - Fanni, Salvatore C.; Febi, Maria; Colligiani, Leonardo; Volpi, Federica; Ambrosini, Ilaria; Tumminello, Lorenzo; Aghakhanyan, Gayane; Aringhieri, Giacomo; Cioni, Dania; Neri, Emanuele (Frontiers in Radiology, 2023)
The aim of this systematic review was to evaluate the state of the art of radiomics in testicular imaging by assessing the quality of radiomic workflow using the Radiomics Quality Score (RQS) and the Quality Assessment of Diagnostic Accuracy Studies-2 (QUADAS-2). A systematic literature search was performed to find potentially relevant articles on the applications of radiomics in testicular imaging, and 6 final articles were extracted. The mean RQS was 11,33 ± 3,88 resulting in a percentage of 31,48% ± 10,78%. Regarding QUADAS-2 criteria, no relevant biases were found in the included papers in the patient selection, index test, reference standard criteria and flow-and-timing domain. In conclusion, despite the publication of promising studies, radiomic research on testicular imaging is in its very beginning and still hindered by methodological limitations, and the potential applications of radiomics for this field are still largely unexplored.